Simulation of ball handling in overhead passing in volleyball - Okauchi, M.; Maeda, H.; Shimada, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2000)
The purpose of this study was to obtain basic data for teaching ball handling in overhead passing in volleyball. The method used was simulation of a mass-elasticity-viscosity model consisting of arms, hands and ball. First, we calculated the acceleration of the ball during contact with the hands through VTR images. As a result of comparing this acceleration with that of the simulation of the model, we found the model to be proper, and the coefficients of elasticity and viscosity were adequate. The coefficients indicated that a skilled player changes hand elasticity depending on the height of set up. This is the reason skilled players can control the ball accurately. On the other hand, unskilled players can not change hand elasticity well, which affects their control of the ball.